Application of digital marketing innovation in creative industries in Waringinkurung Village, Serang Regency - Gunawan, Akbar; Barleany, Dhena Ria; Putri, Ardini; Khairunnisa, Zahra (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
The creative industry is a growing business sector that draws significant attention due to its reliance on skills and talents, which improve welfare and create employment opportunities. One example is Mrs. Riris' scrunchie production business, a Micro, Small, and Medium Enterprise (MSME) located in Waringin Kurung Village/Subdistrict, Serang Regency. This business has a production capacity of up to 200 pieces per month. Still, it lacks essential elements such as a brand identity, logo, and proper product packaging, relying solely on word-of-mouth marketing. Similarly, other creative industry businesses in Waringin Kurung Village/Subdistrict face challenges from limited knowledge and skills in utilizing information technology for business growth. This community service program aims to provide counseling and assistance to creative industry business actors to foster innovation in digital marketing. The program is implemented in several stages: initial socialization, training on innovative approaches relevant to the creative industry, and practical implementation. Activities include counseling, hands-on assistance, and website development to expand marketing reach. This initiative is expected to empower local businesses to improve their competitiveness and achieve sustainable growth by adopting digital marketing strategies.Industri kreatif merupakan sektor usaha yang sedang berkembang pesat dan banyak diminati karena mengandalkan keterampilan dan bakat yang dimilikinya untuk meningkatkan kesejahteraan dan menciptakan lapangan kerja. Salah satu contohnya adalah usaha produksi scrunchie milik Ibu Riris, sebuah Usaha Mikro Kecil dan Menengah (UMKM) yang berlokasi di Desa/Kecamatan Waringin Kurung, Kabupaten Serang. Usaha ini memiliki kapasitas produksi hingga 200 potong per bulan. Namun, usaha ini masih belum memiliki unsur-unsur penting seperti identitas merek, logo, dan kemasan produk yang baik, sehingga hanya mengandalkan pemasaran dari mulut ke mulut. Begitu pula dengan usaha industri kreatif lainnya di Desa/Kecamatan Waringin Kurung yang menghadapi kendala keterbatasan pengetahuan dan keterampilan dalam memanfaatkan teknologi informasi untuk pengembangan usaha. Program pengabdian masyarakat ini bertujuan untuk memberikan penyuluhan dan pendampingan kepada para pelaku usaha industri kreatif agar mampu berinovasi dalam pemasaran digital. Pelaksanaan program ini dilakukan melalui beberapa tahap, yaitu sosialisasi awal, pelatihan pendekatan inovatif yang relevan dengan industri kreatif, dan pelaksanaan praktik. Kegiatan yang dilakukan meliputi penyuluhan, pendampingan langsung, dan pengembangan situs web untuk memperluas jangkauan pemasaran. Inisiatif ini diharapkan dapat memberdayakan bisnis lokal untuk meningkatkan daya saing mereka dan mencapai pertumbuhan berkelanjutan dengan mengadopsi strategi pemasaran digital.